Underappreciated layers of antibody-mediated immune synapse architecture and dynamics - Benjamin S. Goldberg; Margaret E. Ackerman (mBio)
ABSTRACT The biologic activities of antibody drugs are dictated by structure-function relationships—emerging from the kind, composition, and degree of interactions with a target antigen and with soluble and cellular antibody receptors of the innate immune system. These activities are canonically understood to be both modular: antigen recognition is driven by the heterodimeric antigen-binding fragment, and innate immune recruitment by the homodimeric constant/crystallizable fragment. The model that treats these domains with a high degree of independence has served the field well but is not without limitations. Here, we consider how new insights, particularly from structural studies, complicate the model of neat biophysical separation between these domains and shape our understanding of antibody effector functions. The emerging model endeavors to explain the phenotypic impact of both antibody intrinsic characteristics and extrinsic features—fitting them within a spatiotemporal paradigm that better accounts for observed antibody activities. In this review, we will use insights from recent models of classical complement complexes and T cell immune synapse formation to explore how structural differences in antibody-mediated immune synapses may relate to their functional diversity.